Penyelesaian Perundingan Perjanjian Kerja Bersama (PKB) Yang Tidak Menemui Kesepakatan (Studi Kasus di PJT I Malang) - Zainal Ariﬁn; Emi Puasa Handayani; Saivol Firdaus (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
The Collective working Agreement (PKB) is regulated in Article 1601 of the Civil Code (Civil Code), which is an agreement between two parties, an employee or laborer and a company, both bound together. Workers commit themselves to employers for a certain time. A bond to do work by receiving wages. Another understanding of collective working agreements is regulated in Law Number 13 of 2003 concerning labor. Working agreements are agreements between employers and employees, or laborers who have conditions of employment, rights and obligations of both parties. There are two research questions, ﬁ rst what is the meaning of the settlement of collective bargaining agreements that do not meet the agreement and, how do we formulate a joint working agreement negotiation solution without ﬁnding a deal. The method used to answer research questions is a type of normative and empirical legal research. Theories used are certainty theory, hierarchical theory of law and distributive justice theory. The results achieved. First, the meaning of the deadlock negotiation agreement to formulate a co-operation agreement. Two, settlement of collective working agreement negotiations that did not meet the agreement, can be completed with three mechanisms. The ﬁ rst is done through bipartite negotiations, through conciliation and mediation mechanisms.ﬁ nally the dispute mechanism can be carried out in industrial relations courts.